ANALYSIS OF SUCCESS DRIVERS OF E-HEALTH INFRASTRUCTURE AND USE: A NATIONAL LEVEL STUDY - BAGCHI, KALLOL K.; Udo, Godwin J. (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
e-Health, in form of websites that contain information on health, is emerging as an important resource for common people in some developed nations. The purpose of the study is to explore the critical factors that drive the e-Health infrastructure of nations and its usage. Research data from a set of more than 40 developed and developing nations were gathered from 8,000 websites to allow analysis of factors driving the e-Health growth. The results suggest that at a national level, cost of health care per capita and perception of health are significant in e-Health infrastructure regression, explaining more than 32-41% of the variability in e-Health infrastructure. Confidence in health care systems, perception of good health, health care costs, and human development index and health infrastructure also explain over 69-78% of the variability in e-Health use.